PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP HASIL BELAJAR IPAS PADA SISWA KELAS IV MEDAN SUNGGAL TAHUN AJARAN 2025/2026 - Stevani Gulo, Santa Putri; Sihombing, Imelda; Margareta Sinaga, Eka; Sinaga, Reflina; Pinem, Irmina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Jigsaw cooperative learning model on the learning outcomes of Natural and Social Sciences (IPAS) in fourth-grade students of SDN 060914 Medan Sunggal in the 2025/2026 academic year. The main problem in this study is the low learning outcomes of students in IPAS caused by monotonous conventional learning, centered on the teacher, and the lack of use of visual media. This type of research is quantitative with an experimental method (Pre-Experimental Design) in the form of One-Group Pretest-Posttest Design. The study population includes all fourth-grade students of SDN 060914 Medan Sunggal, totaling 54 students. Sampling was carried out using a purposive sampling technique, so that class IVB, totaling 27 students, was selected as the experimental class. Data collection techniques used multiple-choice tests, student response questionnaires, and documentation. The research instrument was tested for validity using the Product Moment correlation formula and for reliability using Cronbach's Alpha using SPSS 22. The test results showed a reliability index of 0.936 for the test item and 0.904 for the questionnaire, both of which are considered very strong. A significant improvement in students' social studies learning outcomes after implementing the Jigsaw learning model was demonstrated through a hypothesis test (t-test) with a significance value (2-tailed) of <0.05. Furthermore, student questionnaire responses indicated a very positive response to the implemented model.